Implementasi Sistem Real Time Peringatan Kebakaran Pada Terminal Listrik Rumah Tangga - Muhamad Irfanul Hadi; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Increased use of electricity because all equipment requires an energy source. And electricity is the energy source that is most widely used in various equipment. Because more and more electricity users need a system to monitor electricity usage. There are several studies that make a system for monitoring electricity use. Existing systems are limited to monitoring electricity usage without a security system. While electricity is the cause of most of Indonesia's fires according to the central statistics agency. Because there is still no system that can detect fires due to electricity, a realtime fire warning system is created at the household electricity terminal. This study uses FreeRTOS to process sensor data. In this study, reading the current sensor, voltage sensor and temperature sensor will be more accurate in reading. Reading using FreeRTOS will produce eroor at a temperature sensor of 0.609%, a voltage sensor of 0.685% and a temperature sensor of 2.02%. Whereas when using a sequential program or an ordinary program it will produce an error of 2.219% on the current sensor, 1.05% on the voltage sensor and 4.607% this proves that there is an error difference of 1.61% on the current sensor, 0.365% on the voltage sensor and 2.587% on the sensor temperature is compared without using the FreeRTOS method with better accuracy. However, when using FreeRTOS the execution time will be 89.3 ms longer than without using FreeRTOS. With such high accuracy the system can detect that there will be a fire accurately and give the notification appropriately.